We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
130
8
avatar

1. The graphs of y = x^3 - 3x + 2 and x + 4y = 4 intersect in the points \((x_1,y_1), (x_2,y_2)\), and \((x_3,y_3)\). If \(x_1 + x_2 + x_3 = A\) and \(y_1 + y_2 + y_3 = B\), compute the ordered pair (A,B).

 

2. Compute \(\frac{2 + 6}{4^{100}} + \frac{2 + 2 \cdot 6}{4^{99}} + \frac{2 + 3 \cdot 6}{4^{98}} + \dots + \frac{2 + 98 \cdot 6}{4^3} + \frac{2 + 99 \cdot 6}{4^2} + \frac{2 + 100 \cdot 6}{4}\).

 

3. A sequence \((a_n)\) is defined as follows: \(a_1 = 1, a_2 = \frac{1}{2},\) and \(a_n = \frac{1 - a_{n - 1}}{2a_{n - 2}}\) for all \(n \ge 2.\) Find \(a_{120}.\)

 

Thank you!

 Jun 18, 2019
 #1
avatar+23048 
+2

1.
The graphs of \(y = x^3 - 3x + 2 \text{ and } x + 4y = 4\) intersect in the points \((x_1,y_1), (x_2,y_2), \text{ and } (x_3,y_3)\).
If \(x_1 + x_2 + x_3 = A \text{ and } y_1 + y_2 + y_3 = B\), compute the ordered pair \((A,B)\).

 

\(\mathbf{\text{Vieta:}} \)

\(\begin{array}{rcll} x^3+ a_2x^2+a_1x+a_0 &=& 0 \qquad \mathbf{ a_2 =-(x_1+x_2+x_3)} \\ \end{array}\)

 

\(\begin{array}{|rcll|} \hline x + 4y &=& 4 \quad |\quad y = x^3 - 3x + 2 \\ x + 4(x^3 - 3x + 2) &=& 4 \\ 4x^3-11x+4 &=& 0 \quad |\quad : 4 \\ x^3-\dfrac{11}{4}x+1 &=& 0 \quad |\quad a_2 = 0~ !\\\\ \mathbf{x_1+x_2+x_3 } &=& \mathbf{0} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline x + 4y &=& 4 \\ x &=& 4-4y \\ \mathbf{x} &=& \mathbf{4(1-y)} \\\\ y &=& x^3 - 3x + 2 \quad |\quad \mathbf{x = 4(1-y)}\\ y &=& 64(1-y)^3 -3\cdot 4(1-y)+2 \\ \ldots \\ 64y^3-129y^2+181y-54 &=& 0 \quad |\quad : 64 \\ y^3-3y^2+\dfrac{181}{64}y-\dfrac{54}{64} &=& 0 \quad |\quad a_2 = -3~ !\\\\ -(y_1+y_2+y_3) &=& a_2 \\ -(y_1+y_2+y_3) &=& -3 \\ \mathbf{y_1+y_2+y_3 } &=& \mathbf{3} \\ \hline \end{array} \)

 

\(\mathbf{(A,B) = (0,3)}\)

 

laugh

 Jun 18, 2019
 #6
avatar
+1

Thank you so much, heureka! I really appreciate all your help. 

Guest Jun 19, 2019
 #2
avatar+23048 
+2

2.
Compute
\(\dfrac{2 + 6}{4^{100}} + \dfrac{2 + 2 \cdot 6}{4^{99}} + \dfrac{2 + 3 \cdot 6}{4^{98}} + \dots + \dfrac{2 + 98 \cdot 6}{4^3} + \dfrac{2 + 99 \cdot 6}{4^2} + \dfrac{2 + 100 \cdot 6}{4}\)

 

\(\text{AP: $\quad a_n = a_1+(n-1)d,\qquad a_1=2,\ d=6 $} \)

\(\begin{array}{|rcll|} \hline a_n&=&2+(n-1)\cdot6\\\\ a_2 &=& 2+1\cdot 6 = 8 \\ a_3 &=& 2+2\cdot 6 \\ \ldots \\ a_{101} &=& 2+100\cdot 6 =602\\ \hline \end{array}\)

 

\(\text{GP: $\quad b_n = ar^{n-1},\qquad a=1,\ r=\dfrac{1}{4} $} \)

\(\begin{array}{|rcll|} \hline b_n &=& \left(\dfrac{1}{4}\right)^{n-1} \\\\ b_1 &=& \left(\dfrac{1}{4}\right)^{0} = 1 \\ b_2 &=& \dfrac{1}{4} \\ b_3 &=& \left(\dfrac{1}{4}\right)^{2} \\ \ldots \\ b_{101} &=& \left(\dfrac{1}{4}\right)^{100} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline s &=& \dfrac{2 + 6}{4^{100}} + \dfrac{2 + 2 \cdot 6}{4^{99}} + \dfrac{2 + 3 \cdot 6}{4^{98}} + \dots + \dfrac{2 + 98 \cdot 6}{4^3} + \dfrac{2 + 99 \cdot 6}{4^2} + \dfrac{2 + 100 \cdot 6}{4} \\ \hline \end{array}\)

\(\begin{array}{|rclll|} \hline s &=& a_2b_{101}+& a_3b_{100}+a_4b_{99}+\ldots+ a_{101}b_{2} \\ \dfrac{s}{\frac{1}{4}} &=& & a_2b_{100}+ a_3b_{99}+\ldots+ a_{100}b_{2}+a_{101}b_1 \quad | \quad b_1 = 1,\ a_{n+1}-a_n = d \\ \hline s- \dfrac{s}{\frac{1}{4}} &=& a_2b_{101}+& d(b_2+b_3+\ldots + b_{100})-a_{101} \quad | \quad a_2 = 8,\ a_{101} = 602,\ d = 6 \\ -3s &=& 8b_{101}+& 6(\underbrace{b_2+b_3+\ldots + b_{100}}_{=S~ (GP)})-602 \\ -3s &=& 8b_{101}+& 6S-602 \\\\ &&&\begin{array}{|rclll|} \hline S &=& b_2+&b_3+\ldots + b_{100} \\ \dfrac{1}{4}S &=& & b_3+\ldots + b_{100}+b_{101} \\ \hline S - \dfrac{1}{4}S &=& b_2-& b_{101} \\ \dfrac{3}{4}S &=& b_2-& b_{101} \\ S &=& \dfrac{4}{3}b_2-& \dfrac{4}{3}b_{101} \\ \hline \end{array} \\\\ -3s &=& 8b_{101}+& 6\left(\dfrac{4}{3}b_2- \dfrac{4}{3}b_{101} \right)-602 \\ -3s &=& 8b_{101}+& 8b_2- 8b_{101} -602 \\ -3s &=& & 8b_2 -602 \quad | \quad b_2 = \dfrac{1}{4} \\ -3s &=& & 2 -602 \\ -3s &=& & -600 \quad | \quad : (-3) \\ \mathbf{ s} &=& &\mathbf{ 200 } \\ \hline \end{array}\)

 

\(\mathbf{\dfrac{2 + 6}{4^{100}} + \dfrac{2 + 2 \cdot 6}{4^{99}} + \dfrac{2 + 3 \cdot 6}{4^{98}} + \dots + \dfrac{2 + 98 \cdot 6}{4^3} + \dfrac{2 + 99 \cdot 6}{4^2} + \dfrac{2 + 100 \cdot 6}{4} = 200}\)

 

laugh

 Jun 18, 2019
 #3
avatar+23048 
+2

3.
A sequence \((a_n)\) is defined as follows: \(a_1 = 1,\ a_2 = \dfrac{1}{2}\), and \(a_n = \dfrac{1 - a_{n - 1}}{2a_{n - 2}}\) for all \(n > 2\). Find \(a_{120}\).

 

\( a(1) = 1 \\ a(2) = 1/2 \\ a(3) = 1/4 \\ a(4) = 3/4 \\ a(5) = 1/2 \\ a(6) = 1/3 \\ a(7) = 2/3 \\ a(8) = 1/2 \\ a(9) = 3/8 \\ a(10) = 5/8 \\ a(11) = 1/2 \\ a(12) = 2/5 \\ a(13) = 3/5 \\ a(14) = 1/2 \\ a(15) = 5/12 \\ a(16) = 7/12 \\ a(17) = 1/2 \\ a(18) = 3/7 \\ a(19) = 4/7 \\ a(20) = 1/2 \\ a(21) = 7/16 \\ a(22) = 9/16 \\ a(23) = 1/2 \\ a(24) = 4/9 \\ a(25) = 5/9 \\ a(26) = 1/2 \\ a(27) = 9/20 \\ a(28) = 11/20 \\ a(29) = 1/2 \\ a(30) = 5/11 \\ a(31) = 6/11 \\ a(32) = 1/2 \\ a(33) = 11/24 \\ a(34) = 13/24 \\ a(35) = 1/2 \\ a(36) = 6/13 \\ a(37) = 7/13 \\ a(38) = 1/2 \\ a(39) = 13/28 \\ a(40) = 15/28 \\ a(41) = 1/2 \\ a(42) = 7/15 \\ a(43) = 8/15 \\ a(44) = 1/2 \\ a(45) = 15/32 \\ a(46) = 17/32 \\ a(47) = 1/2 \\ a(48) = 8/17 \\ a(49) = 9/17 \\ a(50) = 1/2 \\ a(51) = 17/36 \\ a(52) = 19/36 \\ a(53) = 1/2 \\ a(54) = 9/19 \\ a(55) = 10/19 \\ a(56) = 1/2 \\ a(57) = 19/40 \\ a(58) = 21/40 \\ a(59) = 1/2 \\ a(60) = 10/21 \\ a(61) = 11/21 \\ a(62) = 1/2 \\ a(63) = 21/44 \\ a(64) = 23/44 \\ a(65) = 1/2 \\ a(66) = 11/23 \\ a(67) = 12/23 \\ a(68) = 1/2 \\ a(69) = 23/48 \\ a(70) = 25/48 \\ a(71) = 1/2 \\ a(72) = 12/25 \\ a(73) = 13/25 \\ a(74) = 1/2 \\ a(75) = 25/52 \\ a(76) = 27/52 \\ a(77) = 1/2 \\ a(78) = 13/27 \\ a(79) = 14/27 \\ a(80) = 1/2 \\ a(81) = 27/56 \\ a(82) = 29/56 \\ a(83) = 1/2 \\ a(84) = 14/29 \\ a(85) = 15/29 \\ a(86) = 1/2 \\ a(87) = 29/60 \\ a(88) = 31/60 \\ a(89) = 1/2 \\ a(90) = 15/31 \\ a(91) = 16/31 \\ a(92) = 1/2 \\ a(93) = 31/64 \\ a(94) = 33/64 \\ a(95) = 1/2 \\ a(96) = 16/33 \\ a(97) = 17/33 \\ a(98) = 1/2 \\ a(99) = 33/68 \\ a(100) = 35/68 \\ a(101) = 1/2 \\ a(102) = 17/35 \\ a(103) = 18/35 \\ a(104) = 1/2 \\ a(105) = 35/72 \\ a(106) = 37/72 \\ a(107) = 1/2 \\ a(108) = 18/37 \\ a(109) = 19/37 \\ a(110) = 1/2 \\ a(111) = 37/76 \\ a(112) = 39/76 \\ a(113) = 1/2 \\ a(114) = 19/39 \\ a(115) = 20/39 \\ a(116) = 1/2 \\ a(117) = 39/80 \\ a(118) = 41/80 \\ a(119) = 1/2 \\ a(120) = 20/41 \)

 

laugh

 Jun 18, 2019
 #4
avatar
0

2 - ∑[(6*n + 2) / 4^(100 - n +1), n , 1, 100] = 200

 Jun 18, 2019
 #5
avatar
0

3 - This sequence has this recurrence relation:
a(n + 3) =((n + 2) a(n))/(n + 6) + a(n + 1)/(-n - 6) + a(n + 2)/(-n - 6) + 3/(n + 6): Where:
a(1) = 1
a(2) = 1/2
a(3) = 1/4
a(4) = 3/4
.
.
.
.
a(120) = 1/123 (119 a(117) - a(118) - a(119) + 3)
a(120) = 20 / 41

 Jun 18, 2019
 #7
avatar
+1

Thank you very much as well, guest! Again, I appreciate it :)

Guest Jun 19, 2019
 #8
avatar+23048 
+1

3.
A sequence \((a_n)\) is defined as follows: \(a_1 = 1,\ a_2 = \dfrac{1}{2}\), and \(a_n = \dfrac{1 - a_{n - 1}}{2a_{n - 2}}\) for all \(n > 2\). Find \(a_{120}\).

 

\( a_n =\begin{cases} \dfrac{1}{2}, & \text{if }n\equiv 2 \pmod{3} \\\\ \dfrac{n}{2n+6}, & \text{if }n\equiv 0 \pmod{3} \\\\ \dfrac{n+5}{2n+4}, & \text{if }n\equiv 1 \pmod{3} \\ \end{cases}\)

 

\(\begin{array}{|rcll|} \hline n &=& 120 \quad \text{ and }\quad 120 &\equiv& 0 \pmod{3} \\ \\ a_{120} &=& \dfrac{n}{2n+6} \\\\ &=& \dfrac{120}{2\cdot 120+6} \\\\ &=& \dfrac{120}{246} \\\\ \mathbf{a_{120}} &=& \mathbf{\dfrac{20}{41}} \\ \hline \end{array}\)

 

laugh

 Jun 19, 2019

39 Online Users

avatar
avatar